The Every Woman Study (EWS) in Kenya: Identifying challenges and opportunities to improve survival and quality of life for women with ovarian cancer (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Ovarian cancer is the second most common cause of death among gynecological cancerpatients in Kenya, and the number of cases is predicted to rise from 1,130 to 2,600 per year by 2040.However, there is very limited diagnostic and treatment capacity. This study aims to establish the first-ever patient experience evidence base of women with ovarian cancer in Kenya and identify challengesand opportunities to improve survival and quality of life.Methods: This was a prospective cross-sectional observational study in which all eligible womenattending Moi Teaching and Referral and Aga Khan Hospitals with a diagnosis of ovarian cancer withinthe previous five years were recruited.Results: Of 104 eligible women with a median age of 51 years, epithelial ovarian cancers were the mostcommon (70%), particularly high-grade serous carcinoma (46%). Most respondents (66%) had advanceddisease. Approximately 24% had to travel for five hours or more to access care. The mean average timefrom experiencing symptoms to diagnosis was 7.4 months. Almost half had never heard of ovariancancer. Approximately 81% reported that their finances had been affected largely by the diagnosis, with55% of these women reporting that their household income had dropped below what they needed tosurvive.Conclusion: The inaccessibility of quality cancer care in Kenya leads to delays in diagnosis andtreatment initiation. Innovative awareness strategies, health provider education, and cost mitigation areneeded to ensure that women can seek help promptly to reduce morbidity and mortality.